Deteksi Virus yang Menginfeksi Kedelai di Jawa - Yunita Fauziah Rahim; Tri Asmira Damayanti; Munif Ghulamahdi (Jurnal Fitopatologi Indonesia, 2015)
Virus infection is an important production constraint for soybean. Research was conducted to detect virus infection from soybean samples collected from several locations in Java. Leave samples from 50 plants was taken randomly from each location in Bogor, Cirebon, Bantul, and Ponorogo. Field symptoms was observed and disease incidence was determined based on serological assay using specific antibodies to Cucumber mosaic virus (CMV), Soybean mosaic virus (SMV), Cowpea mild mottle virus (CPMMV), and Bean pod mottle virus (BPMV). Incidence of CMV, SMV, and CPMMV was 72–84%, 14–24%, and 6–8%, respectively; whereas infection of BPMV was not found. Specific viral DNA of CMV, Potyvirus, and Geminivirus was successfully amplified using specific primer for CMV coat protein, universal primer for Potyvirus and Geminivirus, respectively. Nucleotide sequence analysis showed that isolate CMV from soybean has the highest homology (99%) to CMV strain S, Potyvirus isolates has the highest homology (90%) to BCMV isolate Mungbean from China and BCMV strain Blackeye from Vietnam, and Geminivirus isolates has the highest homology (96%) to Pepper yellow leaf curl virus (PYLCV) from Bogor and Java. Phyllogenetic analysis showed that CMV strain S formed